Electronic health records with Epic and IBM FlashSystem 9100 Blueprint Version 2 Release 2. (IBM Corporation, 2019)
This information is intended to facilitate the deployment of IBM® FlashSystem for the Epic Corporation electronic health record (EHR) solution by describing the requirements and specifications for configuring IBM FlashSystem® 9100 and its parameters. The document also describes the steps that are required to configure the server that host the EHR application. To complete the tasks, you must have a working knowledge of IBM FlashSystem 9100 and Epic applications. The information in this document is distributed on an "as is" basis, without any warranty that is either expressed or implied. Support assistance for the use of this material is limited to situations where IBM FlashSystem storage devices are supported and entitled and where the issues are not specific to a blueprint implementation.